2017
DOI: 10.1371/journal.pone.0171938
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of traction force measurement in vacuum extraction: Development of a multivariate prognostic model

Abstract: ObjectiveTo enable early prediction of strong traction force vacuum extraction.DesignObservational cohort.SettingKarolinska University Hospital delivery ward, tertiary unit.Population and sample sizeTerm mid and low metal cup vacuum extraction deliveries June 2012—February 2015, n = 277.MethodsTraction forces during vacuum extraction were collected prospectively using an intelligent handle. Levels of traction force were analysed pairwise by subjective category strong versus non-strong extraction, in order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The characteristics of study populations showed that pregnant women and fetuses or newborns were the populations of most studies developed using LR and non-LR models, respectively. Among pregnant women, the LR algorithm was mostly applied to develop predictions for outcome categories of obstetric labor (13/77, 17%) [36,46,47,54,57,62,64,70,83,86,91,97,103], pregnancy-induced hypertension (12/77, 16%) [30,31,43,48,55,65,66,68,76,81,93,105], and gestational diabetes (7/77, 9%) [33,45,49,84,94,100,104]. Among fetus or newborn populations, non-LR algorithms were mostly applied to develop predictions for outcome categories of premature birth (12/50, 24%) [111,112,115,116,118,119,121,122,125,130,141,143] and fetal distress (9/50, 18%) [113,…”
Section: Lr and Other Machine Learning Algorithmsmentioning
confidence: 99%
“…The characteristics of study populations showed that pregnant women and fetuses or newborns were the populations of most studies developed using LR and non-LR models, respectively. Among pregnant women, the LR algorithm was mostly applied to develop predictions for outcome categories of obstetric labor (13/77, 17%) [36,46,47,54,57,62,64,70,83,86,91,97,103], pregnancy-induced hypertension (12/77, 16%) [30,31,43,48,55,65,66,68,76,81,93,105], and gestational diabetes (7/77, 9%) [33,45,49,84,94,100,104]. Among fetus or newborn populations, non-LR algorithms were mostly applied to develop predictions for outcome categories of premature birth (12/50, 24%) [111,112,115,116,118,119,121,122,125,130,141,143] and fetal distress (9/50, 18%) [113,…”
Section: Lr and Other Machine Learning Algorithmsmentioning
confidence: 99%
“…Latterly there has also been the introduction of single-use systems and a focus on feedback mechanisms to inform best practice (e.g. alarms to alert the clinician to loss of suction [92][93][94] and force sensors to detect the level of traction 62,95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both exposures may also be afflicted with a general highlighting effect that we believe is inevitable when all personnel are participating in a specific project, a concept known as the Hawthorne effect [22]. The equipment and results of traction force measurement have been described in detail by the authors elsewhere [21, 23].…”
Section: Methodsmentioning
confidence: 99%